Contemporary Marketing Research / Fourth Edition - Gates Roger; Mcdaniel Carl (South-Western, 1999)
This book offers everything from project proposals and links to online academic journals to career information. An Introduction to Market Research, Creating a Research Design, Data Acquisition, Data Analysis, Market Research in Action, Comprehensive Cases, Statistical Tables, Glossary, Index.